1992
DOI: 10.1111/j.1465-7295.1992.tb01536.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gender‐sorting on Propensity to Coauthor: Implications for Academic Promotion

Abstract: A cohort sample of Ph.D. economists indicates a significant propensity for researchers to select coauthors of the same sex. This gender‐sorting contributes to lower article production for women. Further, we find evidence of bias in academic promotion when single‐authored and coauthored articles carry the same weight in promotion and salary decisions. The evidence explains, in part, why women academics wait longer for promotion and are not as likely to be promoted as men. Among the effects of gender‐sorting is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 14 publications
9
119
1
5
Order By: Relevance
“…Sauer (1988) shows that 1/n discounting is not rejected by data on salaries and publications, but Moore, Newman and Turnbull (1995) find in comparable salary-based data that departments do not discount joint authored papers significantly. 21 Palmer (1983), McDowell andSmith (1992) and Schinski, Kugler and Wick (1998) report the result of surveys that in determining salaries and promotions, universities do not typically fully discount coauthored work by the number of authors. 22 Granting agencies and universities often encourage collaboration, apparently in the belief that such teamwork is likely to result in better research.…”
Section: Teamwork Determined Exogenouslymentioning
confidence: 99%
See 1 more Smart Citation
“…Sauer (1988) shows that 1/n discounting is not rejected by data on salaries and publications, but Moore, Newman and Turnbull (1995) find in comparable salary-based data that departments do not discount joint authored papers significantly. 21 Palmer (1983), McDowell andSmith (1992) and Schinski, Kugler and Wick (1998) report the result of surveys that in determining salaries and promotions, universities do not typically fully discount coauthored work by the number of authors. 22 Granting agencies and universities often encourage collaboration, apparently in the belief that such teamwork is likely to result in better research.…”
Section: Teamwork Determined Exogenouslymentioning
confidence: 99%
“…McDowell and Smith (1992) use cross-sectional data on academics and regress the number of articles produced by an individual (with co-authored 1 See McDowell and Melvin (1983) and Durden and Perri (1995) on economics. In other fields, the increase in coauthorship has also been noted.…”
Section: Introductionmentioning
confidence: 99%
“…McDowell and Smith (1992) reject the hypothesis according to which the weighting of coauthored articles in the promotion of academics is equal to the inverse of the number of coauthors. The authors use answers to a questionnaire given to 378…”
Section: The Issue Of Cooperation Among Researchersmentioning
confidence: 99%
“…By examining a cohort sample of PhD economists, McDowell and Smith (1992) found that researchers tend to collaborate with those of the same sex. When modeling the coauthorship patterns during 1991-2002 in three top economics journals, Boschini and Sj€ ogren (2007) found that females tend to collaborate with same-gender authors.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, as we examined the effects of the authors' research similarities on their collaborations, the top research interest of each author was included. We are also interested in how the authors' gender (McDowell & Smith, 1992) plays a role in their collaboration; thus, we collected the authors' gender information. In total, we collected the following six attributes for each author:…”
Section: Datamentioning
confidence: 99%